Influence of preconditioning and blocking on accuracy in solving Markovian models - Bylina, Beata; Bylina, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
The article considers the effectiveness of various methods used to solve systems of linear equations (which emerge while modeling computer networks and systems with Markov chains) and the practical influence of the methods applied on accuracy. The paper considers some hybrids of both direct and iterative methods. Two varieties of the Gauss elimination will be considered as an example of direct methods: the LU factorization method and the WZ factorization method. The Gauss-Seidel iterative method will be discussed.
Keywords: preconditioning; linear equations; blocking methods; Markov chains; WZ factorization